Translation as Politics: The Translation of Sadako Kurihara’s War Poems - Hayakawa, Atsuko (TTR, 2012)
The dynamic power shift of the world picture from a dominant hegemonic power structure to a global consciousness of hybridity accelerated by postcolonialism in the late 20th century has opened up a way to re-read history from a new perspective. The major point in the process is the recognition of both the cultural and political others which had long been made invisible and silent by the politics of power. It is in this light that translation must be addressed by scholarly discourse.This paper focuses on war poems by Sadako Kurihara both in the time of and after the censorship that occurred during the occupation. Through the lens of translation and its modalities, I would propose here, history can be re-addressed. How the narrative of translation creates an arena where an individual voice is made to be heard in the language of others is closely related with the translator’s stance in the political context. The task of the translator today is much more important than ever, not only culturally but also ethically.